A field guide to Christianity - Allan, John, 1950-; Eyre, Gus. (Chicago : Moody Press, 1987, 1986)
Previously published as: Express checkout. c1986. "Answering common misconceptions"--Cover.
Keywords: APOLOGETICS; CHRISTIANITY -- MISCELLANEA